ANALISIS PERPINDAHAN PANAS KIT TAMBAL BAN PORTABLE TERHADAP VARIASI WAKTU PENAMBALAN - Usman; Sentiyaki Sentiyaki; Dwi Nurhudaeni Abdullah (JURNAL ILMIAH MOMENTUM, 2025)
Motorcycles are the primary mode of transportation in Indonesia, with a total of 125,305,332 units recorded in 2022 according to the Central Bureau of Statistics. One of the common problems faced by riders is tire leakage, which can disrupt travel. This study aims to design a portable tire patching tool based on a heating element, utilizing a piston pump mechanism and powered by a motorcycle battery, compactly assembled to fit within the motorcycle’s luggage compartment. The research method employed is experimental, using a thermal imaging device to determine the optimal temperature range for melting the tire patch rubber. The results show that 2 minutes of heating produces a bonding strength of 45.7 Psi. Starting from an ambient temperature of 30 °C, the heating plate reached 139.5 °C, while the tire surface reached 118.3 °C. The total heat transfer energy generated was 3,845,356.8 Joules. The resulting patch adhesion effectiveness reached 70.4%. This tool is considered effective for use in areas with limited access to tire repair services and can be operated directly by riders to reduce the risk of unexpected expenses during travel.